PKM Pelatihan Microsoft Excel Sebagai Penunjang Keterampilan Hard Skill Bagi Guru-Guru SDN Depok Baru 3 - Amalia, Rini; Sagita, Sri Melati; Faisal, Ahmad (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Advances in information and communication technologies have brought about significant changes in various aspects of life, including the world of education. Teachers today are demanded to possess strong technological skills to face challenges and take advantage of opportunities. It is expected that the use of information technology could enhance the skills for hard skill support of teachers in schools. One of the supporting hard skills that teachers should possess is the ability to use Microsoft Excel applications. In addition to basic knowledge of Microsoft Excel teachers are expected to be able to process report scores. By using Microsoft Excel application it is expected to provide ease in calculating or processing student report scores especially for the teachers especially the principal teachers. By conducting Microsoft Excel application training, it is expected that teachers can operate Microsoft Excel application in calculating students’ grades or report grades processing.